Acute hepatitis C patient knowledge and practices regarding their self-care management directed for prevention of complications - Abrar Ali Wazqar,; Bilqis Ahmed Alshareef,; Samaher Sahal Malibari,; Najla Fadaa Alrowis,; Hind Mohammed Hmod Albashiri,; Hanan Mohammed Al thomali,; Abed Ahmed A Al Thagafi,; Fawaz Mohammed Alghamdi,; Saleha Salem Faraj Allah Al-Thameli,; Faisal Ayidh Alsubaie, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Hepatitis C virus (HCV) infection is a major cause of liver cirrhosis. Globally, 177.5 million people are infected with HCV. The aim of this study was to assess acute hepatitis C patient knowledge and practices regarding their self-care management directed for prevention of complications. Research design: A descriptive research design was used. Setting: this study was conducted in medical departments, Erada complex and mental health, Taif, Saudi Arabia. Sample: A purposive sample of 120 acute hepatitis C patients admitted in the previous mentioned setting. Tool: Patients’ interviewing questionnaire that included the following parts; socio demographic characteristics, knowledge and self-reported practice assessment regarding self-care management. Results: More than half of studied subjects had unsatisfactory knowledge score and adequate practice score regarding self-care management. There was no statistically significant relation between patients' knowledge and their demographic data. There were statisticallysignificant relations between patients’ practice and their demographic data; marital status, educational level and gender. While, there were no statistically significant relation betweenpatients’ practice and age, residence, occupation, monthlyincome P˃0.05. Conclusion: Nearly two thirds of the studied subjects had unsatisfactory knowledge score regarding HCV and self-care management for complications prevention. However, more than half of them had adequate self-care management practice. The study recommended that development of health education program for HCV patients and their families to teach them how to apply self-care management practices for complications prevention is very important.